Kristal Hemoglobin pada Bercak Darah yang Terpapar dengan Beberapa Sabun Mandi Antiseptik Padat Menggunakan Tes Teichmann dan Tes Takayama - Umara, Mutia; Asni, Enikarmila; Indrayana, Mohammad Tegar (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2016)
ABSTRACTIn the criminals like murder, torture, and rape usually found bloodstains, blood, sperm, saliva, and hair at the criminals scene. In the some forensic examination of blood are confirmatory test (Teichmann test and Takayama test) that can confirm if suspected object were blood. The way in which often wipe out blood using solid antiseptic bath soap. The purpose of this research was to know description of hemoglobin crystal on bloodstains that exposed by solid antiseptic bath soap with Teichmann test and Takayama test. The design of this research was experimental. Samples of this research were 26 bloodstains slides (2 control slides and 24 slides that have been exposed with 6 kind of solid antiseptic bath soap). The showed 24 bloodstains slides (100%) had positive result with Teichmann test and Takayama test, and there were no changes of crystal’s shape. It could be conclude that hemoglobin crystals still could be found in bloodstains that exposed by solid antiseptic bath soap with Teichmann test and Takayama test.Keywords: Hemoglobin crystals, Bloodstains, Solid antiseptic bath soap, Teichmann test, Takayama test